Health Education Needs Patient Diagnosed with Heart Failure - Alanazi, Mariam (British Journal of Healthcare and Medical Research, 2023)
Heart failure (HF) is a severe, frequent hospitalization and extensive treatment strategies are hallmarks of a progressing clinical condition. One-third to one-half of these hospitalizations are believed to be avoidable (Zaharova, 2019). To enhance patient outcomes and eliminate unnecessary patient recruitment, the SS Consensus Guidelines promote self-care and adherence to treatment regimens. Effective ways to take care of yourself include promoting healthy habits and ongoing monitoring and treatment of symptoms (Rice et al., 2018). Ineffective self-care was explained by the lack of information about specific diseases. Clinicians focus on gaining knowledge by educating patients on how to plan for heart failure to manage this problem (HF-MP).